Otimização da adesão de filmes de DLC sobre aço SAE 4140 utilizando intercamadas contendo silício depositadas a partir de tetrametilsilano - Piroli, Vanessa (My University, 2022)
Diamond-like carbon (DLC) films have been gaining space in the automotive, aeronautical, biomedical and decorative industries due to their low coefficient of frictionand high wear resistance. However, the low adhesion between the DLC film and ferrous alloys represents an obstacle to its application. The use of Si-containing interlayers aims to improve the adhesion of the films. However, the need for high temperatures in the deposition of the interlayers makes technological applications unfeasible. Therefore, hydrogen etching is considered an alternative to improve the overall adhesion of the films, through a chemical cleaning of the interlayer surface with hydrogen plasma. Hydrogen etching is applied after the deposition of the Si-containing interlayer. This work aims to evaluate the effect of hydrogen etching on the adhesion of DLC films to SAE 4140 steel, in systems with Si-containing interlayers, obtained from tetramethylsilane (TMS) and deposited at low temperatures (starting at 85 °C). Two sets of samples were deposited, called (1) series with hydrogen etching and (2) series without hydrogen etching, which differ from each other only by the presence of hydrogen etching. The interlayer's deposition temperature was varied in the two series. The scratch test showed adhesion of the DLC films for all deposition temperatures of the series without hydrogen etching, with critical loads ranging from 4 N to 6 N. The series with hydrogen etching showed partial delamination in some deposition conditions. According to the results of glow-discharge optical emission spectroscopy (GDOES), the hydrogen etching removed considerable amounts of elements such as C, Si and O from the interface between the DLC film and the Si-containing interlayer. This contributed to the reduction of the interlayer's thickness. Raman spectroscopy and Fourier-transform infrared spectroscopy (FTIR) characterized the DLC films and the Si-containing interlayers as hydrogenated amorphous carbon (a-C:H) and hydrogenated amorphous silicon carbide (a-SiCx:H), respectively. Oxygen contents below ~5% were measured by X-ray photoelectron spectroscopy (XPS) at the interfaces and at the interlayer of the series without hydrogen etching. It was concluded that the good adhesion of the DLC films of the samples of the series without hydrogen etching (at temperatures as low as 85 °C) is a consequence of the low oxygen content present in the structure and the use of a low background pressure (~0.8 Pa) in the deposition system. This work observed that (1) the application of hydrogen etching is not necessary to ensure adhesion of DLC films in processes with low deposition temperatures of Si-containing interlayers, formed from TMS and deposited in systems with low background pressure as ~0.8 Pa; (2) it is possible to deposit well-adhered DLC films in systems with Si-containing interlayers (formed from TMS) deposited at temperatures as low as 85 °C. [resumo fornecido pelo autor]
Filmes de carbono tipo diamante (DLC) vêm ganhando espaço na indústria automotiva, aeronáutica, biomédica e decorativa devido ao seu baixo coeficiente de atrito e elevada resistência ao desgaste. Entretanto, a baixa adesão entre o filme de DLC e ligas ferrosas representa um obstáculo para sua aplicação. O uso de intercamadas contendo Si visa melhorar a adesão dos filmes. Contudo, a necessidade de elevadas temperaturas na deposição das intercamadas inviabiliza aplicações tecnológicas. Nesse sentido, o etching de H2 é utilizado para melhorar a adesão geral dos filmes, através da limpeza química da superfície da intercamada com plasma de H2. O etching de H2 é aplicado após a deposição da intercamada contendo Si. Esse trabalho tem como objetivo avaliar o efeito do etching de H2 na adesão de filmes de DLC sobre o aço SAE 4140, em sistemas com intercamadas contendo Si, obtidas a partir de tetrametilsilano (TMS) e depositadas em baixas temperaturas (iniciando em 85 °C). Foram depositadas duas séries de amostras, denominadas (1) série com etching de H2 e (2) série sem etching de H2, que diferem entre si somente pela presença do etching de H2. Variou-se a temperatura de deposição da intercamada nas duas séries. Os resultados dos testes de riscamento mostraram adesão dos filmes de DLC para todas as temperaturas de deposição da série sem etching de H2, com cargas críticas variando de 4 N a 6 N. A série com etching de H2 apresentou delaminação parcial em algumas condições de deposição. De acordo com os resultados de espectroscopia de emissão óptica por descarga luminescente (GDOES), o etching de H2 retirou considerável teores de elementos como C, Si e O da interface entre o filme de DLC e a intercamada contendo Si. Isso contribuiu para a redução da espessura da intercamada. Análises de espectroscopia Raman e espectroscopia no infravermelho por transformada de Fourier (FTIR) caracterizaram os filmes de DLC e as intercamadas contendo Si como filmes de carbono amorfo hidrogenado (a-C:H) e carbeto de silício amorfo hidrogenado (a-SiCx:H), respectivamente. Teores inferiores a ~5% de oxigênio foram medidos por espectroscopia de fotoelétrons excitados por raios-X (XPS) nas interfaces e no interior da intercamada da série sem etching de H2. Concluiu-se que a boa adesão dos filmes de DLC das amostras da série sem etching de H2 (em temperaturas tão baixas como 85 °C) é consequência do baixo teor de oxigênio presente na estrutura e do uso de baixa pressão de base (~0,8 Pa) no sistema de deposição. Esse trabalho observou que (1) a aplicação do etching de H2 não é fundamental para a adesão de filmes de DLC em processos com baixas temperaturas de deposição de intercamadas contendo Si, formadas a partir do precursor TMS e depositas em sistemas com pressão de base tão baixas como ~0,8 Pa; (2) é possível depositar filmes de DLC bem aderidos, em sistemas com intercamadas contendo Si (formadas a partir de TMS) depositadas em temperaturas tão baixas quanto 85 °C. [resumo fornecido pelo autor]
Keywords: Ciência dos materiais; Materiais - Testes; Filmes finos de diamantes; Carbono - Aplicações industriais; Adesão; Materials science; Materials - Test; Diamond thin films; Carbon - Industrial applications; Adhesion